UPAYA MENINGKATKAN MINAT BACA MASYARAKAT MELALUI RUMAH LITERASI DAN PERPUSTAKAAN KELILING DI DESA MONTONG ARE - Ermiana, Ida; Daefullah, Adibia; Hadi, Muhammad Pauzul; Putri, Carika Yulia; Ayura, Adinda Putri; Khotimah, Baiq Husnul; Shakila; Algifari, M. Ghazi; Latifah, Nurul; Nurmayanti; Rizani, Rafli (Universitas Mataram, 2025)
Reading interest among Indonesian communities remains relatively low, including in Montong Are Village, Kediri District, West Lombok. Observations show that the majority of residents, particularly children and adolescents, tend to spend more time on gadgets than on reading activities. To address this issue, the KKN PMD-Literasi team from the University of Mataram implemented the Literacy House and Mobile Library programs as strategic initiatives to foster a reading culture in the community. This study employed a qualitative descriptive approach, utilizing direct observation and documentation to assess the community’s reading interest. The results indicated that the Literacy House successfully attracted children to read regularly through the provision of illustrated books, interactive programs such as read-aloud sessions, storytelling, creative writing classes, and traditional games as engagement tools. Meanwhile, the Mobile Library reached remote hamlets, enabling children with limited access to the Literacy House to participate in reading activities. Both programs demonstrated positive impacts in increasing reading interest, boosting the frequency of visits to literacy facilities, and reducing gadget dependency among children and adolescents in Montong Are Village.